Phonon Confinement Effect in Two-dimensional Nanocrystallites of Monolayer MoS2 to Probe Phonon Dispersion Trends Away from Brillouin-Zone Center*Supported by the National Natural Science Foundation of China under Grant Nos 11225421, 11474277, 11434010 and 11574305, and the National Young 1000 Talent Plan. (May 2016) - Shi 石, Wei 薇; Zhang 张, Xin 昕; Li 李, Xiao-Li 晓莉; Qiao 乔, Xiao-Fen 晓粉; Wu 吴, Jiang-Bin 江滨; Zhang 张, Jun 俊; Tan 谭, Ping-Heng 平恒
Abstract : The fundamental momentum conservation requirement q 0 for the Raman process is relaxed in the nanocrystallites (NCs), and phonons away from the Brillouin-zone center will be involved in the Raman scattering, which is well-known as the phonon confinement effect in NCs. This usually gives a downshift and asymmetric broadening of the Raman peak in various NCs. Recently, the A′1 mode of 1L MoS2 NCs is found to exhibit a blue shift and asymmetric broadening toward the high-frequency side [Chem. Soc. Rev. 44 (2015) 2757 and Phys. Rev. B 91 (2015) 195411]. In this work, we carefully check this issue by studying Raman spectra of 1L MoS2 NCs prepared by the ion implantation technique in a wide range of ion-implanted dosage. The same confinement coefficient is used for both E′ and A′1 modes in 1L MoS2 NCs since the phonon uncertainty in an NC is mainly determined by its domain size. The asymmetrical broadening near the A′1 and E′ modes is attributed to the appearance of defect-activated phonons at the zone edge and the intrinsic asymmetrical broadening of the two modes, where the anisotropy of phonon dispersion curves along Γ–K and Γ–M is also considered. The photoluminescence spectra confirm the formation of small domain size of 1L MoS2 nanocrystallites in the ion-implanted 1L MoS2 . This study provides not only an approach to quickly probe phonon dispersion trends of 2D materials away from Γ by the Raman scattering of the corresponding NCs, but also a reference to completely understand the confinement effect of different modes in various nanomaterials.